Islamic consumerism: the decisionmaking behaviour on halal products with halal logo - Mohamad Tauhid, Dinie Kaiyisah; Atan, Rodziah; Arshad, Syariena (Universiti Islam Pahang Sultan Ahmad Shah, 2022)
The objective of this research is to find factors in consumers' decision-making behaviour toward halal products that influence them to purchase halal products. Halal products are the only product that Muslim consumers can use and consume since it is according to Sharia law. Due to this, Muslim consumers will always look for a halal product with a halal logo on the packaging. With halal logos, consumers will be more confident since they trust halal logos that have been authorised by JAKIM. Non-Muslims also will perceive halal product that has label on them as it is considered hygiene, safety and quality. However, consumers still have to be careful when purchasing halal products since there is a lot of misuse of halal logos. Hence, it is conducted by doing an analysis of other research or study papers to find the factor of consumers' decision-making behaviour toward halal products, whether consumers purchase halal products with logos or not. Based on this study, consumers of halal products decide to use products that have the halal logo because they are confident and believe that the product is safe to use.